Sports Participation in Children and Adolescents with Immune Thrombocytopenia (ITP). Issue 12 (14th July 2015) - Kumar, Manjusha; Lambert, Michele P.; Breakey, Vicky; Buchanan, George R.; Neier, Michelle; Neufeld, Ellis J.; Kempert, Pamela; Neunert, Cindy E.; Nottage, Kerri; Klaassen, Robert J.; on behalf of the ITP Consortium of North America
<x xml:space="preserve">Abstract</x> We surveyed 278 pediatric hematologists/oncologists regarding how children with immune thrombocytopenia (ITP) are counseled for participation in sports. Results show substantial variation in physician perception of contact risk for different sports, and the advice offered about restriction of sport activities of affected children. Many physicians recommend restriction of sports when platelet counts are under 50 × 109/L. Such restriction may affect the child's quality of life despite their having an overall benign disease. Pediatr Blood Cancer © 2015 Wiley Periodicals, Inc.